2016
DOI: 10.1002/gcc.22377
|View full text |Cite
|
Sign up to set email alerts
|

The 5q deletion size in myeloid malignancies is correlated to additional chromosomal aberrations and to TP53 mutations

Abstract: Deletions in the long arm of chromosome 5 (del(5q)) are recurrent abnormalities in myeloid malignancies. We analyzed del(5q) and accompanying molecular mutations in MDS, MPN and MDS/MPN cases. A high del(5q) frequency was revealed in MDS (1869/11398 cases; 16%), followed by MDS/MPN (37/1107; 3%) and MPN (97/6373; 2%). To investigate potential associations of the del(5q) size with the respective phenotypes, we applied array CGH analyses in selected cohorts of 61 MDS, 22 MDS/MPN and 23 MPN cases. The size varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Episomal reprogramming has identified del(5q) as an early cytogenetic lesion with the capacity to perturb genome stability and differentiation [ 6 ]. Larger del(5q) size has been correlated with higher mutation frequency [ 5 ], which in this case included the somatic driver mutations: TET2, TP53 , SF3B1 , and ASXL1 at high allele frequency (Table 1 ). We propose that this combination led to HSC injury and disease progression through sub-clone branching (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Episomal reprogramming has identified del(5q) as an early cytogenetic lesion with the capacity to perturb genome stability and differentiation [ 6 ]. Larger del(5q) size has been correlated with higher mutation frequency [ 5 ], which in this case included the somatic driver mutations: TET2, TP53 , SF3B1 , and ASXL1 at high allele frequency (Table 1 ). We propose that this combination led to HSC injury and disease progression through sub-clone branching (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of MPN to acute lymphoblastic leukemia (ALL) is rare, with only seventeen cases reported in the literature [ 3 ]. Retrospective studies suggest that genetic defects, including allele burden, order of mutation acquisition, clonal heterogeneity and epigenetic mechanisms play an important role in the observed conversion rate, as well as the varied clinical-pathologic entities that evolve [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively slow rate of progression of the TP53 -mutated patients during AZA therapy may be still relatively well tolerated by the patients thus guaranteeing a survival benefit. It is also an important point that the mutations operate with other mutations in concert and thus higher occurrence of preceding 5q- aberration may have added to selection (during clonal evolution) of distinct TP53 mutations (observed in up to 31% of 5q- patients) [ 16 ] that are not as aggressive and still may provide certain cell-survival benefit for maturing blood elements to maintain residual hematopoiesis while preventing rapid progression to MDS/AML.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive markers remain scant even with the help of CMA. Specifically, response to lenalidomide among MDS patients with del(5q) and TKI resistance among CML patients did not correlate with CMA findings even though additional CNAs found by array and TP53 mutations/17p deletions are associated with disease progression and worse prognosis [60,62].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…One study that assessed these patients for response to lenalidomide showed no significant difference in the response of patients with 5q deletions as the sole abnormality and those with additional abnormalities detected by CMA[60].Despite the lack of correlation with treatment response, one study identified significant differences in OS between patients with del(5q) as the sole abnormality by karyotype (median OS = 34 months) compared to 5q abnormalities (loss and CN-LOH) identified by CMA only (OS = 15 months)[14]. Furthermore, using CMA to refine 5q deletion breakpoints, Stengel et alhave shown in MDS, MPN and MDS/MPN cases that the size of 5q deletion correlated with the number of additional CNAs detected by array, and TP53 mutations were correlated with a larger del(5q) size and with disease progression and worse prognosis[62].…”
mentioning
confidence: 99%